Factors affecting UPM students' purchase intention for branded sportswear - Md Jusoh, Zuroni; Yah, Goh Chyi; Abu Bakar, Elistina; Zainudin, Norzalina; Osman, Syuhaily (Human Resource Management Academic Research Society (HRMARS), 2023)
Sportswear has become a staple in consumers' wardrobes, regardless of whether they intend to play sports or simply look sporty. Hence, this study determines the influence of factors such as attitude, subjective norm, perceived behavioural control, price, and brand image on consumers’ purchase intention towards branded sportswear among UPM students. A total of 250 respondents were involved in this study through questionnaires as research instruments via simple random sampling. Data were analyzed using the Statistical Package for Social Science (SPSS) for Windows version 28.0. Pearson correlation test was used to examine the relationship between attitude, subjective norm, perceived behavioural control, price, and brand image with consumers’ purchase intention. The results of the analysis showed attitude (r = 0.716, p = 0.001), subjective norm (r = 0.647, p = 0.001), perceived behavioural control (r = 0.467, p = 0.001), price (r = 0.660, p = 0.001), and brand image (r = 0.677, p = 0.001) had significant relationship with consumers’ purchase intention towards branded sportswear. The findings of Multiple Linear Regression analysis found that attitude (B = 0.318) is the most dominant factor in affecting consumers’ purchase intention towards branded sportswear among UPM students. The results of this study have made some contributions to the knowledge about consumers’ purchase intentions for branded sportswear and the Theory of Planned Behavior (TPB).